Four‐year outcome of randomly assigned lifestyle treatments in primary care of children with obesity. (30th October 2018) - Forsell, Christer; Gronowitz, Eva; Larsson, Yvonne; Kjellberg, Britt‐Marie; Friberg, Peter; Mårild, Staffan
Abstract: Aim: To assess the four‐year outcome in children with obesity randomised to one of two 12‐month lifestyle treatment programmes in primary care. Methods: At baseline, 64 children with obesity aged 8.0–13.0 years were randomised to a treatment programme managed either by a nurse, dietician and physiotherapist (n = 32) or by a nurse and dietician (n = 32). Results: From baseline to follow‐up, the mean body mass standard deviation score (BMISDS) had decreased by −0.50 [standard deviation (SD) 0.73], p = 0.002, in the nurse, dietician and physiotherapist group (n = 27), by −0.26 (SD 0.73), p = 0.057 in the other group (n = 29); adjusted mean difference was −0.22, 95% confidence interval −0.59; 0.16, p = 0.25. Changes in weight categories did not differ between the groups: both had a change from obesity to normal weight in 1 and to overweight in 6; in the physiotherapist group 1 case of severe obesity changed to obesity. The combined treatment groups (n = 56) had a mean reduction in BMISDS of −0.37 (SD 0.73) and an improved distribution in weight categories, p = 0.015. Conclusion: After four years, there was no difference in outcome between the treatment options. In the treatment groups combined the number of children with obesity and their adiposity measures were significantly lower. Abstract :